The lampenflora in show caves and its treatment: an emerging ecological problem - Estévez, Carlos Baquedano; Merino, Luis Moreno; Román, Almudena de la Losa; Valsero, Juan J Durán (International journal of speleology, 2019)
The artificial lighting of caves adapted for touristic visits, leads to the appearance and propagation of a complex community of phototrophic organisms known as "lampenflora". Formed mainly by algae and cyanobacteria, they produce the degradation of the colonized substrates and decrease the show value of the caves. This phenomenon became famous worldwide in the 1960s due to the damage caused to the paintings in the Lascaux Cave (France). Since then it has become an issue of serious concern to both managers of show caves and to the international scientific community. Over time, the problem has been approached following two complementary strategies: preventing colonization by the invading organisms or eliminating them once they have become established through the use of chemical products, mainly biocides and strong oxidants. This kind of treatment generates pollutant effluents that can move the problem from the walls of the caves to the groundwater. This paper presents a critical literature review of the problem and the proposed solutions, and emphasizes the need for further study of the optimal doses of treatment chemicals and to develop quantitative methods to determine their effectiveness.